2022
DOI: 10.3389/fcell.2021.810635
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin-E Mediated Pyroptosis—A Novel Mechanism Regulating Migration, Invasion and Release of Inflammatory Cytokines in Rheumatoid Arthritis Fibroblast-like Synoviocytes

Abstract: Synovium fibroblast-like synoviocytes (FLSs) are important participants in the pathogenesis of synovitis and joint destruction in rheumatoid arthritis (RA). Pyroptosis is a pro-inflammatory and cell lytic programmed cell death mechanism mediated by gasdermin (GSDM) family proteins. In this study, we demonstrated the increased expression of GSDME and increased levels of GSDME-mediated pyroptosis in RA synovial tissues. In vitro, stimulation with TNF-α plus hypoxia mimicking the inflammatory and hypoxic environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“… 26 Similarly, Gasdermin E (GSDME) level is reported to be upregulated in the synovial macrophages and synovial fibroblasts of OA and RA synovium and its deficiency mitigated synovitis in mouse models of RA. 74 , 75 In addition, we speculated a role for Gasdermin C (GSDMC) in OA as its upstream regulator, caspase-6, 76 was shown to be upregulated in chondrocytes exposed to mechanical stress in the ACLT rat osteoarthritis model. 77
Figure 5 Pyroptotic pathways related to OA The canonical pyroptotic pathway involves the activation of caspase-1 activity leading to the cleavage of GSDMD through the activation of nod-like receptor (NLR) proteins.
…”
Section: Caspase Activation Mediates Inflammation and Pyroptosis In Oamentioning
confidence: 99%
“… 26 Similarly, Gasdermin E (GSDME) level is reported to be upregulated in the synovial macrophages and synovial fibroblasts of OA and RA synovium and its deficiency mitigated synovitis in mouse models of RA. 74 , 75 In addition, we speculated a role for Gasdermin C (GSDMC) in OA as its upstream regulator, caspase-6, 76 was shown to be upregulated in chondrocytes exposed to mechanical stress in the ACLT rat osteoarthritis model. 77
Figure 5 Pyroptotic pathways related to OA The canonical pyroptotic pathway involves the activation of caspase-1 activity leading to the cleavage of GSDMD through the activation of nod-like receptor (NLR) proteins.
…”
Section: Caspase Activation Mediates Inflammation and Pyroptosis In Oamentioning
confidence: 99%
“…These two signaling pathways, which are responsible for the cleavage of GSDME and GSDMD, might mutually support one another. For the caspase‐3/GSDME axis, TNF‐α in combination with hypoxia could induce pyroptosis via this pathway 120 . The role of TNF in activating pyroptosis in RA via the caspase‐3/GSDME signaling pathway was again confirmed by Zhai et al 121 …”
Section: Pyroptosis In Inflammatory Bone Diseasesmentioning
confidence: 86%
“…For the caspase-3/GSDME axis, TNF-α in combination with hypoxia could induce pyroptosis via this pathway. 120 The role of TNF in activating pyroptosis in RA via the caspase-3/GSDME signaling pathway was again confirmed by Zhai et al 121 Moreover, Wu et al 122 found that acid-sensitive ion channels (ASICs) mediated pyroptosis in chondrocytes taken from rats with adjuvant arthritis. The underlying process may be connected to the capacity of ASIC1a to encourage the influx of Ca 2+ to initiate the calpain-2/ calcineurin axis, which ultimately activates caspase-1 after contributing to the aggregation and assembly of the NLRP3 inflammasome.…”
Section: Rheumatoid Arthritismentioning
confidence: 87%
See 1 more Smart Citation
“…A little more accurately, programmed‐mediated cell death can be classified into two forms: lytic and non‐lytic cell death. Lytic cell death often consists of necroptosis and pyroptosis that can cause leakage of intracellular components, promote release of inflammatory cytokines, and lead to following inflammatory response, which is known as inflammatory death or inflammatory necrosis 12,13 . And non‐lytic cell death (usually referred to as apoptosis) manifests when cells can be eliminated by phagocytes but without an inflammatory response 14 .…”
Section: Death Of Chondrocytesmentioning
confidence: 99%